The Effect of Servant Leadership, Organizational Culture and Work Creative Behavior on HR Performance Study on Central Java Tribune: Study on Central Java Tribune - Puspita Widyantoro, B Mayang; Setyorini, Noni; Indriasari, Ika (INTERNATIONAL CONFERENCE OF ECONOMICS AND BUSINESS, 2025)
This study examines the influence of Work Creative Behavior, Servant Leadership, and Organizational Culture on employee performance at the Central Java Tribune. Using a survey method on 67 employees, validity and reliability tests were conducted to ensure the accuracy of the research instrument. Multiple linear regression analysis shows that the three variables have a positive and significant influence on employee performance. Work Creative Behavior improves performance through creative ideas and innovation. Servant Leadership, which supports employee development, contributes positively to performance. In addition, a conducive Organizational Culture was shown to encourage better employee performance. This research shows the importance of strengthening work creativity, implementing servant leadership, and developing a strong organizational culture to improve employee performance at the Central Java Tribune. The practical implication is that management must focus on performance improvement strategies through these three aspects.